An all-digital semi-blind clock and data recovery system. Issue 4 (April 2015) - Abdallah, Mina; Eladawy, Ahmed; Mohieldin, Ahmed
Abstract This paper presents a digitally intensive semi-blind clock and data recovery (SBCDR) system. The paper covers the theory, analysis, and system level simulation of this SBCDR. The proposed CDR is tailored to target the optical network standard OC-192. The SBCDR can provide the required jitter tolerance (JTo), and still provide enough jitter filtering to achieve the jitter transfer (JTr) requirements. Also, the recovered clock achieves a low jitter generation (JG) of 0.01 UIrms and 0.0064 UIrms for both the wide-band and high-band jitter filters defined by the standard. The proposed SBCDR provides two advantages over typical SBCDRs and PLL-based CRDs that target OC-192. First, the digitally intensive nature provides a scalable and process tolerant design. Second, the architecture provides a CDR that can pass all three jitter performance metrics, without the aid of an external clean-up phase locked loop (PLL) or a high performance clock multiplication unit (CMU) typically required by OC-192 transceivers. By utilizing a circular representation for the phase calculation in the over-sampling clock and data recovery (OSCDR), extensive pipe-lining in the implementation and higher data rate tolerance can be achieved. The simulation results of the proposed SBCRD agree closely with theoretical results.